La imagen relatada - Dupleich, Julieta Laura (2018)
This paper develops research experiences with blind people in the Project "Habitat and blindness. Construction of spatial knowledge and its mental representation" The expressive resource of the story makes photography and painting possible and accessible languages by widening the world view. The listening and the oral narration of any image, allows us to communicate and get closer. Telling from our profession of architects our gaze and recreating the sensations as if it were happening, what an author / artist wanted to transmit at a certain time, so that blind people can also build their own image of what is described.